Targeted Next Generation Sequencing Identifies Novel Mutations in RP1 as a Relatively Common Cause of Autosomal Recessive Rod-Cone Dystrophy. (6th January 2015) - El Shamieh, Said; Boulanger-Scemama, Elise; Lancelot, Marie-Elise; Antonio, Aline; Démontant, Vanessa; Condroyer, Christel; Letexier, Mélanie; Saraiva, Jean-Paul; Mohand-Saïd, Saddek; Sahel, José-Alain; Audo, Isabelle; Zeitz, Christina
Abstract : We report ophthalmic and genetic findings in families with autosomal recessive rod-cone dystrophy (arRCD) and RP1 mutations. Detailed ophthalmic examination was performed in 242 sporadic and arRCD subjects. Genomic DNA was investigated using our customized next generation sequencing panel targeting up to 123 genes implicated in inherited retinal disorders. Stringent filtering coupled with Sanger sequencing and followed by cosegregation analysis was performed to confirm biallelism and the implication of the most likely disease causing variants. Sequencing identified 9 RP1 mutations in 7 index cases. Eight of the mutations were novel, and all cosegregated with severe arRCD phenotype, found associated with additional macular changes. Among the identified mutations, 4 belong to a region, previously associated with arRCD, and 5 others in a region previously associated with adRCD. Our prevalence studies showed that RP1 mutations account for up to 2.5% of arRCD. These results point out for the necessity of sequencing RP1 when genetically investigating sporadic and arRCD. It further highlights the interest of unbiased sequencing technique, which allows investigating the implication of the same gene in different modes of inheritance. Finally, it reports that different regions of RP1 can also lead to arRCD.